Does Teno Torque Virus Induce Autoimmunity After Hematopoietic Stem Cell Transplantation? A Case Report. - Maximova, Natalia; Pizzol, Antonio; Ferrara, Giovanna; Maestro, Alessandra; Tamaro, Paolo (J Pediatr Hematol Oncol, 2015)
Teno Torque virus, member of the family of Anelloviridae, has been associated with many autoimmune diseases such as idiopathic hepatitis, systemic lupus erythematosus, and multiple sclerosis. Its viral load tends to be higher in the bone marrow and in tissues with high turnover rate. We report here a case of an 11-month-old infant affected by acute myeloid leukemia who underwent hematopoietic stem cell transplantation, and after 6 months had autoimmune hepatitis and atopic dermatitis. Extremely high-cytokine IP-10 and eotaxin levels were found in her sera, and serological tests and RT-PCR for viruses showed positive results exclusively for Teno Torque virus.
Keywords: Autoimmune Diseases; Autoimmunity; Dermatitis, Atopic; DNA Virus Infections; DNA, Viral; Female; Hematopoietic Stem Cell Transplantation; Hepatitis; Humans; Infant; Leukemia, Myeloid, Acute; Prognosis; Torque teno virus; Viral Load